Psychosocial Job Dimensions and Distress/Well-Being: Issues and Challenges in Occupational Health Psychology - Anthony J. Montgomery (Frontiers Research Topics, 2018)
Over the last three decades a large body of research has showed that psychosocial job dimensions such as time pressure, decision authority and social support, could have significant implications for psychological distress and well-being. Theoretical models, such as the job demand-control-social support model (JDCS model), the effort-reward imbalance model (ERI model), the job demands-resources model (JDR model) and the vitamin model suggest that distress and positive dimensions at work (well being and motivation) can be considered as two sides of the same coin. If the job is designed to provide the right mix of psychosocial job dimensions (e.g., optimal time pressure, decision authority and social support), work can boost job engagement and well-being as well as productive behaviors at work. When the job is not designed in an optimal way (e.g., too much time pressure and too little decision authority) work can trigger stress reactions and burnout. Although some insight has been gained on how job dimensions could predict distress and well-being, and also into the dimensions that might moderate and mediate these associations; research still faces several challenges. Firstly, most of this research has been cross-sectional in nature, thus making it difficult to conclude on the long-term effects of psychosocial job dimensions. Another challenge concerns how the contextual dimensions can be incorporated into micro-levels models on employee stress and well-being. Nowadays, work is carried out in the context of a wider environment that includes organizational variables. So far the role of the organizational variables in the theoretical frameworks for explaining the relationships between psychosocial job dimensions, employee distress and well-being, has often been underplayed. The main aim of this research topic is to bring together international research from different theoretical and methodological perspectives in order to advance knowledge and practice in the field of work stress.